紫外線放射計測による温度場の測定 - 吉岡, 信瀬; 黄地, 尚義; 塩飽, 孝志; 大久保, 曙 (溶接学会論文集, 1994)
The accurate measurement of temperature is of great importance in the materials processing such as welding, thermal cutting and heat treatment of metals. The radiation thermometry has a distinct advantage over other temperature detecting method, where it requires no physical contact with the work. The reliability of the thermometry is, however, limited if the emissivity of the work to be measured is not accurately known. According to Planck's law of radiation, it is evident that the effect of temperature on spectral radiance is greater at the shorter wavelengths. In the present paper, the characteristics of UV (ultra-violet) thermometry has been discussed experimentally. The temperature measurement test by UV spot-sensor (spectral range : 0.25 μm) shows that the melting point of Ni can be measured with anaccuracy of ± 1% for any change of the emissivity. The CCD camera with UV-filter, used in this work, made it possible to detect the temperature image on the plate in welding, nearly independent of the emissivity of object.